A sustainable livelihoods framework for the 21st century. (July 2022) - Natarajan, Nithya; Newsham, Andrew; Rigg, Jonathan; Suhardiman, Diana
Highlights: The sustainable livelihoods approach has become a key framework for academic research and in policy circles. The sustainable livelihoods approach has also been widely critiqued. Responding to these critiques but recognising its strengths, this paper sets out a sustainable livelihoods framework for the 21st century. Abstract: This paper proposes a reformulation of the Sustainable Livelihoods Framework (SLF) fit for the 21st century. The article explores the rise and usage of the original SLF, highlighting how its popularity among development practitioners emerged both from its practical focus, and its depoliticization of wider shifts in the development landscape at the time. Distilling the various critiques that have emerged around the use of the SLF and sustainable livelihoods approaches, the article highlights problems of theory, method, scale, historical conceptualisation, politics, and debates on decolonising knowledge. It further explores two key shifts in the global development landscape that characterise the 21st century, namely the impacts of climate change on rural livelihoods, and the shifts wrought by globalisation, before highlighting the structural and relational turns in critical development literature. In speaking to both historical critiques and more recent debates, we present a SLF for the 21st century, foregrounding a structural, spatially-disaggregated, dynamic and ecologically-coherent approach to framing rural livelihoods. We offer a framework and not an approach, hoping that that our SLF leaves open the possibility for different theoretical traditions to better work with emerging rural livelihoods.